2017
DOI: 10.1016/j.bpj.2016.11.3209
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Surface-Driven Self-Assembly and Fatigue-Induced Disassembly of a Virus-Based Nanocoating

Abstract: Self-assembling protein layers provide a ''bottom-up'' approach for precisely organizing functional elements at the nanoscale over a large solid surface area. The design of protein sheets with architecture and physical properties suitable for nanotechnological applications may be greatly facilitated by a thorough understanding of the principles that underlie their self-assembly and disassembly. In a previous study, the hexagonal lattice formed by the capsid protein (CA) of human immunodeficiency virus (HIV) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In fact, in solution (absence of a surface), DENVC is dimeric and does not oligomerize to large particles, as it was observed in many conditions [ 21 , 23 , 50 ]. In agreement with the surface effect, a previous AFM study demonstrated fast and efficient self-assembly of capsid protein from human immunodeficiency virus (HIV) at very low protein concentration when applied directly onto a negatively charged substrate, showing the need for a surface to drive the process [ 46 , 47 ]. Ionic strength, pH, temperature, the concentration of molecules, and molecular sequence can affect surface interactions [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In fact, in solution (absence of a surface), DENVC is dimeric and does not oligomerize to large particles, as it was observed in many conditions [ 21 , 23 , 50 ]. In agreement with the surface effect, a previous AFM study demonstrated fast and efficient self-assembly of capsid protein from human immunodeficiency virus (HIV) at very low protein concentration when applied directly onto a negatively charged substrate, showing the need for a surface to drive the process [ 46 , 47 ]. Ionic strength, pH, temperature, the concentration of molecules, and molecular sequence can affect surface interactions [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 61%
“…Thus, we hypothesize that DENVC self-assembly is surface-driven, as described for other proteins, including viral proteins [ 46 49 ]. In fact, in solution (absence of a surface), DENVC is dimeric and does not oligomerize to large particles, as it was observed in many conditions [ 21 , 23 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human immunodeficiency virus (HIV) capsid consists of ~1,000–1,500 copies of the viral capsid protein 41 , and the self-assembly kinetics of a 2D lattice of this capsid protein has been examined by AFM 42 . Assembly starts at specific sites on the surface, followed by the growth of the lattice and fusion of the different patches, eventually producing full coverage of the surface.…”
Section: Viral Self-assembly Dynamicsmentioning
confidence: 99%
“…For norovirus, the intermediate assembly structure is a double pentamer of dimers, connected by one dimer 39 , whereas for CCMV, half-formed capsids with a lifetime of several seconds have been found 40 . The human immunodeficiency virus (HIV) capsid consists of ~1,000-1,500 copies of the viral capsid protein 41 , and the self-assembly kinetics of a 2D lattice of this capsid protein has been examined by AFM 42 .…”
Section: Box 2 | Experimental Techniquesmentioning
confidence: 99%
“…[16] For many materials (including metals, ceramics and composites), fatigue is by far the most common cause of failure, [17,18] and protein assemblies in general are prone to mechanical failure and highly susceptible to fatigue. [19][20][21][22][23] The susceptibility of protein nanostructures to fatigue may be mitigated, but not compensated, by their self-healing potential, [8,24] observed also in other soft supramolecular materials. [25,26] Thus, there is a strong need for modified protein-based materials with improved mechanical properties.…”
mentioning
confidence: 99%